Books are made out of books : a guide to Cormac McCarthy's literary influences - Crews, Michael Lynn (Southwestern Writers Collection series., 2017)
Michael Lynn Crews thoroughly mines the archive to identify nearly 150 writers and thinkers that McCarthy himself references in early drafts, marginalia, notes, and correspondence. Crews organizes the references into chapters devoted to McCarthy's published works, the unpublished screenplay Whales and Men, and McCarthy's correspondence. For each work, Crews identifies the authors, artists, or other cultural figures that McCarthy references; gives the source of the reference in McCarthy's papers; provides context for the reference as it appears in the archives; and explains the significance of the reference to the novel or play that McCarthy was working on. This groundbreaking exploration of McCarthy's literary influences, impossible to undertake before the opening of the archive, vastly expands our understanding of how one of America's foremost authors has engaged with the ideas, images, metaphors, and language of other thinkers and made them his own.